IMPROVING SIMPLE READING ABILITY IN SLBC STUDENTS CLASS D5 SLB KEMBAR KARYA DEVELOPMENT 3 USED CITIES - Winarti Winarti (Indonesian Journal of Multidisciplinary Science, 2022)
Learning objectives must be a predetermined behavior formulation to belong and appear to students as a result of making learning that has been carried out by the teacher's clarity in conveying, informing and explaining systematically. This study aims to determine how much the increase in learning achievement in reading simple sentences consisting of 3-5 words in mentally retarded children in grade D2 using the drill method. The research method used is Action Research. This study uses the model developed by Kurt Lewin based on the basic concept that action research consists of four main components, namely: Planning (Planning); Action (Acting); Observation (Observing); Reflection (Reflecting). The results of the study on the ability to read simple sentences consisting of 3-5 words, showed that before being given a drill approach class action with picture and picture aids, children became interested in reading word for word simple sentences that were read or spoken to him.